Pengaruh Strategi Promosi dan Fasilitas Pariwisata Terhadap Minat Berkunjung Wisatawan - Sintyawati, Ni Putu Ayu; Wijaya, Putu Yudi; Abiyoga Wulandari, Ni Luh Adisti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The Blooms Garden has problems regarding the increase in the number of visits which are thought to be due to promotion strategies and tourism facilities and the existence of different research results from research gap. This study aims to determine the effect of promotion strategies and tourism facilities simultaneously on interest in visiting The Blooms Garden. The location of this research is located at The Blooms Garden Tourism Object in Br Batusesa, Candikuning Village, Baturiti District, Tabanan, Bali. This study uses quantitative and qualitative data types as well as primary and secondary data sources. The sample of this study amounted to 97 respondents using incidental sampling method as a method of determining the sample. Methods of data collection using observation, interviews, literature study and questionnaires. The data analysis technique used in this research is multiple linear regression analysis. Based on the results of the study, it was shown that either partially or simultaneously the variables of promotion strategy and tourism facilities had a significant positive effect on interest in visiting The Blooms Garden in Tabanan.